Titanium implant with piezoelectric antibacterial performance and preparation method and application thereof
By performing dopamine polymerization, electrospinning and self-polymerization on the titanium implant material, titanium implants with piezoelectric antibacterial properties are formed, which solves the problem that existing materials are susceptible to bacterial infection after implantation, and achieves long-term and stable antibacterial effects and soft tissue integration performance.
Patent Information
- Application Number
- CN202510064396.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
AI Technical Summary
Existing titanium implant materials are susceptible to bacterial infection after implantation, leading to biofilm formation and inflammation, and the existing antibacterial modification strategies have problems such as dose dependence, cytotoxicity and drug-resistant bacteria generation.
By performing dopamine polymerization, electrospinning and self-polymerization treatment on the titanium material, a titanium implant with piezoelectric antibacterial properties is formed. The surface of this material is covered with semi-crystalline thermoplastic polymer @ piezoelectric material @ two-dimensional transition metal carbide nanofiber coating, which can generate piezoelectric potential and reactive oxygen species under mechanical vibration, significantly improving antibacterial properties.
This titanium implant material not only has long-term and stable piezoelectric antibacterial properties, but also promotes soft tissue integration, significantly improves the bacterial effect of the implant, and effectively prevents and treats periimplantitis.
Smart Images

Figure CN119868640A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of dental implant preparation, and relates to a titanium implant with piezoelectric antibacterial performance, and a preparation method and application thereof. Background Art
[0002] Titanium implants have been widely used in the dental field due to their excellent biocompatibility, mechanical properties and corrosion resistance. However, these traditional materials have a significant defect: they do not have bactericidal and antibacterial activity, which makes the implants susceptible to bacterial infection after implantation, forming biofilms, and leading to complications such as peri-implantitis. Implant-related infection and inflammation are the main causes of implant failure, which not only has a serious impact on the health of patients, but also significantly increases medical costs and economic burdens. At present, methods for preventing and treating implant infections include the use of surface coatings or chemical modification strategies such as antibiotics, organic antimicrobial agents, hydrogels, anti-inflammatory cytokines, and metal-organic frameworks. Existing implant surface modification strategies usually rely on drug loading or chemical modification. Although these methods can provide antibacterial effects to a certain extent, they usually have dose-dependent antibacterial activity, may be cytotoxic, or may cause side effects such as the production of drug-resistant bacteria. In addition, the problem of bacterial resistance to antibiotics is also becoming increasingly serious. Therefore, it is particularly important to develop new antibacterial titanium implant materials.
[0003] Patent CN118340936A discloses a repair factor composite bone support material and a preparation method thereof, wherein polylactic acid and KGN composite fibers are loaded on the surface of an alkali-heat-activated titanium alloy by electrospinning to achieve drug loading and sustained release; mesoporous silica obtained by surface activation treatment using plasma immersion ion implantation technology provides biologically active sites to promote the adsorption and proliferation of bone cells; zinc ions are introduced to improve antibacterial properties; silk fibroin modified with methyl methacrylate is added and immersed in an oxidized icariin solution, and a Schiff base reaction occurs between the amino group of the silk fibroin and the aldehyde group of the oxidized icariin, thereby forming a hydrophilic three-dimensional network structure gel structure to stably coat the titanium alloy. However, the patent mentions that the antibacterial property of the material can be improved by introducing zinc ions. However, the release rate and durability of zinc ions in the human body may be affected by many factors, such as the structure of the material, the physiological environment of the human body, etc.; secondly, the material in the patent needs to maintain stable performance in the human body for a long time. However, since the material contains a variety of chemical substances and bioactive factors, the long-term stability of these substances in the human body may be affected by many factors, such as pH value, temperature, enzymatic hydrolysis, etc.; therefore, it is difficult to ensure the long-term effectiveness of the material in the patent in the human body.
[0004] Patent CN111643732A discloses a method for preparing a medical implant material with a titanium dioxide metalloporphyrin coating, comprising the following steps: preparing a titanium dioxide nanocoating on the surface of a pretreated medical titanium or titanium alloy sample by micro-arc oxidation technology, then polymerizing a layer of polydopamine in a dopamine solution, placing the sample in a precursor solution for synthesizing a metalloporphyrin organic framework, inducing in situ growth of a metalloporphyrin organic framework coating on a porous surface by polydopamine, and finally immersing the obtained sample material in a bone active factor material solution for loading. However, the steps such as micro-arc oxidation in the patent require special equipment and instruments, and the purchase and maintenance costs of these equipment are high; secondly, the bonding force between the metalloporphyrin organic framework coating and the titanium dioxide nanocoating and the medical titanium or titanium alloy substrate is an important performance indicator. Insufficient bonding force in the patent causes the coating to fall off or fail during use; and the material prepared in the patent does not have antibacterial properties and is susceptible to bacterial contamination during implantation.
[0005] Patent CN112779780A discloses a process for making antibacterial nonwoven fabrics, including the following steps: the first step is to prepare a hydrophobic antibacterial impregnation liquid; the second step is to perform suede treatment on the surface of the nonwoven fabric, and rub the two sides of the nonwoven fabric with a brush to destroy the texture of the surface of the nonwoven fabric to form a suede surface; the third step is to soak the nonwoven fabric treated in the second step in the hydrophobic antibacterial impregnation liquid obtained in the first step, and after the soaking, the nonwoven fabric is taken out and dried in an oven to constant weight to obtain the antibacterial nonwoven fabric. However, the manufacturing process of this patent involves multiple steps, including the preparation of a hydrophobic antibacterial impregnation liquid, suede treatment on the surface of the nonwoven fabric, and impregnation and drying, etc. These steps require precise control of the reaction conditions and the operating process, which increases the complexity and difficulty of the preparation; secondly, this patent only performs surface physical treatment to form a suede surface, and its surface has insufficient ability to bind to the hydrophobic antibacterial impregnation liquid, and the antibacterial material is easy to fall off. Summary of the invention
[0006] The purpose of the present invention is to overcome at least one defect of the above-mentioned prior art and to provide a titanium implant with piezoelectric antibacterial properties and a preparation method and application thereof. The titanium implant material prepared by the present invention not only has the antibacterial ability of piezoelectric self-excitation, but also has good biocompatibility and the ability to promote soft tissue integration, and is effective in the human body for a long time.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] One of the technical solutions of the present invention is to provide a titanium implant with piezoelectric antibacterial properties, wherein the titanium material is sequentially subjected to dopamine polymerization, electrostatic spinning, and self-polymerization to obtain the titanium implant with piezoelectric antibacterial properties.
[0009] The precursor solution of the electrospinning adopts a semi-crystalline thermoplastic polymer@piezoelectric material@two-dimensional transition metal carbide solution, wherein the semi-crystalline thermoplastic polymer is selected from one or more of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride-trifluoroethylene copolymer (PVDF-TrFE), and 2-oxacycloheptanone homopolymer (PCL), the piezoelectric material is selected from one or more of barium titanate (BaTiO3), lead zirconate titanate (PZT), and lead metaniobate (PbNb2O6), and the two-dimensional transition metal carbide (MXenes) is selected from one or more of Ti3C2 and Ti2C, and the mass ratio of the semi-crystalline thermoplastic polymer, the piezoelectric material and the two-dimensional transition metal carbide is (90-110):(5-15):(0.1-2),
[0010] The self-polymerization precursor solution adopts a polymer conductive monomer-organic sulfonic acid compound solution, the polymer conductive monomer is selected from one or more of 3,4-ethylenedioxythiophene (EDOT), 2,5-dithienylethylene, and pyrrole, the organic sulfonic acid compound is selected from one or more of 3-amino-4-hydroxybenzenesulfonic acid (APS), o-aminoanisole-4-sulfonic acid, and 4-amino-2-hydroxybenzenesulfonic acid, and the usage ratio of the polymer conductive monomer to the organic sulfonic acid compound is (20-40 μL): (0.01-0.2 g).
[0011] Furthermore, the solute of the electrospinning precursor solution is selected from one or more of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMA), and hexamethylphosphoric acid triamide (HMPA), and the dosage ratio of the semi-crystalline thermoplastic polymer to the solute is (0.1-0.5g):(1-5mL).
[0012] Furthermore, when the semi-crystalline thermoplastic polymer, the piezoelectric material and the two-dimensional transition metal carbide are dissolved in a solute, ultrasonic treatment and heating and mixing are performed to obtain a precursor solution for electrospinning.
[0013] The frequency of the ultrasonic treatment is 5-20 kHz, the time is 10-30 min, and the temperature of the heating mixing is 60-100° C., the time is 2-6 h.
[0014] As a preferred technical solution, the temperature of the ultrasonic treatment is 15-40°C.
[0015] As a preferred technical solution, the solute of the self-polymerized precursor solution is water, and the volume ratio of the polymer conductive monomer to the solute is (0.1-0.15):(5-20).
[0016] One of the technical solutions of the present invention is to provide a method for preparing the titanium implant with piezoelectric antibacterial properties, the method comprising the following steps:
[0017] S1, grinding and polishing, ultrasonic cleaning and vacuum drying the titanium material in sequence to obtain a titanium material pretreated by surface activation, and performing dopamine polymerization on the pretreated titanium material;
[0018] S2, immersing the titanium material in an electrospinning precursor solution for electrospinning;
[0019] S3. Immerse the titanium material in a self-polymerizing precursor solution to perform self-polymerization, thereby obtaining a titanium implant with piezoelectric antibacterial properties.
[0020] Furthermore, in step S1, the titanium material is ground and polished using sandpaper with a mesh size of 320-800#, and the roughness of the titanium material itself is eliminated through grinding and polishing to eliminate the influence of the roughness and structure of the coating formed on the surface.
[0021] Use one or more of acetone, ethanol, and water to ultrasonically clean the titanium material. The frequency of a single ultrasonic cleaning is 5-20kHz and the time is 2-10min.
[0022] The temperature of vacuum drying is 40-80°C, the vacuum degree is 0.03-0.1MPa, and the time is 10-30min.
[0023] As a preferred technical solution, the temperatures for grinding and polishing and ultrasonic cleaning in step S1 are both 15-40°C.
[0024] Furthermore, in step S1, the pretreated titanium material is immersed in a precursor solution for dopamine polymerization to perform dopamine polymerization, and a buffer solution and a dopamine solution are dissolved in a solute and the pH is adjusted to obtain a precursor solution for dopamine polymerization.
[0025] The buffer solution is selected from one or more of a tris-hydroxymethylaminomethane hydrochloride (Tris-HCl) solution, a hydroxyethylpiperazineethanesulfonic acid (HEPES) solution, and a borate buffer solution. The concentration of the buffer solution is 5-15 mmol / L. The dopamine solution adopts a dopamine hydrochloride solution. The concentration of the dopamine solution is 0.5-1.5 g / L. The mass ratio of the buffer solution to the dopamine solution is (5-7):(3-5).
[0026] As a preferred technical solution, the solute of the dopamine polymerization precursor solution is water, and the ratio of the buffer solution to the solute is (2-4 g): (1-3 L).
[0027] Furthermore, the pH of the dopamine polymerization precursor solution is 8-9,
[0028] The time for dopamine polymerization in step S1 is 24-48 hours.
[0029] As a preferred technical solution, the temperature of dopamine polymerization in step S1 is 15-40°C.
[0030] Furthermore, in step S2, the flow rate of electrospinning is 0.5-1.5 mL / h, the applied voltage is 10-20 kV, the distance between the electrode and the titanium material is 10-20 cm, and the time is 1-3 h.
[0031] As a preferred technical solution, the temperature of electrospinning in step S2 is 15-40°C.
[0032] Furthermore, in step S3, the temperature of the self-polymerization is 2-10° C., and the time is 12-36 hours.
[0033] One of the technical solutions of the present invention is to provide an application of the titanium implant with piezoelectric antibacterial properties in dental implant restoration.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] (1) Studies have shown that piezoelectric materials such as collagen and mucopolysaccharide in the bone matrix can generate electrical signals under mechanical stimulation, thereby electrically stimulating surrounding cells, promoting cell migration, proliferation, and differentiation, and accelerating tissue repair; the titanium implant material prepared by the present invention simulates the characteristics of natural piezoelectric materials. The surface of the implant is covered with a semi-crystalline thermoplastic polymer @ piezoelectric material @ two-dimensional transition metal carbide nanofiber coating. When subjected to mechanical vibrations generated by an electric toothbrush, it can generate piezoelectric potential and reactive oxygen species (ROS). This piezoelectric self-excitation effect significantly improves the antibacterial properties of the implant, promotes the adhesion and differentiation of fibroblasts, and strengthens the integration of the implant with the host soft tissue, thereby improving the implant. The isolation of bacteria can effectively prevent and treat peri-implantitis and reduce the risk of bacterial infection, showing the great potential of titanium implant materials with excellent piezoelectric antibacterial and implant soft tissue bonding properties in the implant field; semi-crystalline thermoplastic polymers have excellent chemical corrosion resistance, high temperature resistance and electrical insulation properties, and at the same time have certain mechanical strength and toughness, and can be used as suitable nanofiber carriers for electrospinning; two-dimensional transition metal carbides have excellent properties such as high melting point, high hardness, high conductivity, high capacity, and high specific surface area. They also have good electrochemical cycle stability, electrochromic properties, chemical stability, etc., and have good conductive properties, which can promote conductivity;
[0036] (2) In the present invention, the surface of the implant is treated with dopamine polymerization, and the piezoelectric coating can be tightly combined with the titanium implant and is not easy to fall off, thereby ensuring the long-term stability of the piezoelectric coating;
[0037] (3) The polymer conductive monomer and the organic sulfonic acid compound in the present invention can self-polymerize on the surface of the piezoelectric coating, which can improve the conductivity of the material and reduce the potential loss; the organic sulfonic acid compound can participate in the chemical reaction, further improve the conductivity by providing electrons or changing the electron distribution;
[0038] (4) The preparation method of the present invention is simple to operate, highly efficient, low cost, and suitable for large-scale production, which helps to achieve long-term stability and long-term success of dental implants. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a scanning electron microscope (SEM) image of the surface morphology of a titanium implant having piezoelectric antibacterial properties in an embodiment of the present invention;
[0040] Figure 2 This is a test diagram of the hydrophilicity of the titanium implant with piezoelectric antibacterial performance in an embodiment of the present invention;
[0041] Figure 3 This is a piezoelectric performance test diagram of a titanium implant with piezoelectric antibacterial performance in an embodiment of the present invention;
[0042] Figure 4 This is a graph showing the antibacterial activity of the titanium implant in the comparative example of the present invention against Escherichia coli;
[0043] Figure 5 This is a graph showing the antibacterial activity of the titanium implant with piezoelectric antibacterial performance in an embodiment of the present invention against Escherichia coli;
[0044] Figure 6 This is a test diagram of the antibacterial activity of the titanium implant against Staphylococcus aureus in the comparative example of the present invention;
[0045] Figure 7 This is a test diagram of the antibacterial activity of the titanium implant with piezoelectric antibacterial performance against Staphylococcus aureus in an embodiment of the present invention;
[0046] Figure 8 This is a SEM image of the cell morphology on the surface of the titanium implant with piezoelectric antibacterial properties in an embodiment of the present invention. DETAILED DESCRIPTION
[0047] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0048] Unless otherwise specified, the equipment used in the following examples are all conventional equipment in the art; the reagents used are all commercially available products or prepared by conventional methods in the art unless otherwise specified. Anything not described in detail in the following examples can be achieved by conventional experimental means in the art.
[0049] Example:
[0050] A titanium implant with piezoelectric antibacterial properties and a preparation method thereof, the specific steps are as follows:
[0051] S1. The titanium sheet was polished using 400# and 600# water sandpaper at room temperature, and the titanium sheet was ultrasonically cleaned for 5 min at 10kHz using acetone, anhydrous ethanol and deionized water at room temperature, and the titanium sheet was vacuum dried in a vacuum oven at a temperature of 60°C and a vacuum degree of 0.06MPa for 20 min to obtain a titanium sheet pretreated with surface activation, and the pretreated titanium sheet was immersed in a precursor solution of dopamine polymerization at room temperature for 36 hours to polymerize dopamine, wherein the precursor solution of dopamine polymerization is prepared by dissolving 315 mg of 10 mmol / L tris(hydroxymethyl)aminomethane hydrochloride (Tris-HCl) and 200 mg of 1 g / L dopamine hydrochloride in 200 mL of distilled water at room temperature and adjusting the pH to 8.5;
[0052] S2, immersing the titanium sheet in an electrospinning precursor solution at room temperature for electrospinning for 2 hours. The electrospinning precursor solution is prepared by dissolving 0.34 g of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), 0.034 g of barium titanate (BaTiO3) and 0.0034 g of Ti3C2 two-dimensional transition metal carbide (MXenes) in 2 mL of N,N-dimethylformamide (DMF), ultrasonically treating at 10 kHz for 20 minutes at room temperature, and heating and stirring at 80°C for 4 hours. The electrospinning parameters are set to a flow rate of 1 mL / h, an applied voltage of 15 kV, and a distance between the electrode and the titanium sheet of 15 cm.
[0053] S3. Immerse the titanium sheet in a self-polymerizing precursor solution for self-polymerization at 4°C for 24 hours. The self-polymerizing precursor solution is prepared by dissolving 120 μL of 3,4-ethylenedioxythiophene (EDOT) monomer and 0.4 g of 3-amino-4-hydroxybenzenesulfonic acid (APS) in 10 mL of deionized water to obtain a titanium implant with piezoelectric antibacterial properties.
[0054] The titanium implant with piezoelectric antibacterial properties is subjected to the following tests or experiments, and then the test or experiment results are analyzed.
[0055] Test Example 1:
[0056] The surface morphology of the titanium implant with piezoelectric antibacterial properties was tested.
[0057] like Figure 1 As shown, it can be seen that the piezoelectric antibacterial material on the surface of the titanium implant in the embodiment presents a mesh porous structure, and the surface is loaded with barium carbonate particles, Mxene nanosheets and self-polymerized particles, indicating the successful synthesis of the material.
[0058] Test Example 2:
[0059] The hydrophilicity test was performed on the titanium implant with piezoelectric antibacterial properties.
[0060] like Figure 2 As shown, it can be seen that the water contact angle of the titanium implant with piezoelectric antibacterial performance in the embodiment is 19.6°, and the piezoelectric antibacterial material on the surface of the titanium implant is hydrophilic, which is conducive to the adhesion and proliferation of fibroblasts.
[0061] Test Example 3:
[0062] The piezoelectric performance test of the titanium implant with piezoelectric antibacterial performance is carried out, and the specific steps are as follows:
[0063] The frequency used is 1MHz and the power is 1W·cm -2 The titanium implant with piezoelectric antibacterial properties was ultrasonically stimulated for 10 minutes using an ultrasonic instrument.
[0064] like Figure 3 As shown, it can be seen that the piezoelectric antibacterial material on the surface of the titanium implant in the embodiment can generate a stable voltage output under ultrasonic conditions, indicating that a significant piezoelectric effect can be generated.
[0065] Comparative Example:
[0066] A titanium implant using a titanium sheet.
[0067] Test example 4:
[0068] The antibacterial effect of the above titanium implants was tested, and the specific steps were as follows:
[0069] After Escherichia coli and Staphylococcus aureus were co-cultured with the titanium sheet and the titanium implant with piezoelectric antibacterial properties for 24 hours, the frequency was 1 MHz and the power was 1 W cm -2 The cells were stimulated with ultrasound for 10 min and then subjected to plate cloning experiment.
[0070] like Figures 4 to 7 As shown, it can be seen that the number of colonies on the plate of the titanium implant with piezoelectric antibacterial properties in the embodiment is significantly less than that of the titanium sheet in the comparative example, indicating that the piezoelectric antibacterial material on the surface of the titanium implant in the embodiment has a good antibacterial effect.
[0071] Test Example 5:
[0072] The cell morphology test was performed on the surface of the titanium implant with piezoelectric antibacterial properties. The specific steps are as follows:
[0073] Fibroblasts were co-cultured with titanium implants with piezoelectric antibacterial properties for 3 days, with a frequency of 1 MHz and a power of 1 W cm per day. -2 The ultrasonic instrument was used for ultrasonic stimulation for 10 minutes and was applied in dental implant restoration.
[0074] like Figure 8 As shown, it can be seen that the fibroblasts spread and adhere tightly on the surface of the titanium implant with piezoelectric antibacterial properties in the embodiment, indicating that the piezoelectric antibacterial material on the surface of the titanium implant in the embodiment has a positive effect on cell adhesion.
[0075] In summary, after being treated by the method of the present invention, the titanium implant with piezoelectric antibacterial performance prepared in the embodiment has a good biocompatible interface and excellent piezoelectric self-excited antibacterial performance after being treated with dopamine polymerization, electrospinning and self-polymerization.
[0076] The titanium implant constructed by the present invention has the piezoelectric self-excitation antibacterial and soft tissue integration properties. The daily electric toothbrush brushing activity applies vibrations on the tooth surface, which can activate the piezoelectric properties of the piezoelectric material, generate a large number of active groups, and kill the bacteria that infect around the implant. Compared with commonly used implant materials, the present invention has the antibacterial function that general implants do not have, which is beneficial to prevent peri-implantitis caused by bacterial infection.
[0077] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A titanium implant with piezoelectric antibacterial properties, characterized in that: The titanium material was subjected to dopamine polymerization, electrospinning, and self-polymerization in sequence to obtain a titanium implant with piezoelectric antibacterial properties. The precursor solution of the electrospinning adopts a semi-crystalline thermoplastic polymer@piezoelectric material@two-dimensional transition metal carbide solution, wherein the semi-crystalline thermoplastic polymer is selected from one or more of polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-trifluoroethylene copolymer, and 2-oxacycloheptanone homopolymer, the piezoelectric material is selected from one or more of barium titanate, lead zirconate titanate, and lead metaniobate, and the two-dimensional transition metal carbide is selected from one or more of Ti3C2 and Ti2C, and the mass ratio of the semi-crystalline thermoplastic polymer, the piezoelectric material and the two-dimensional transition metal carbide is (90-110):(5-15):(0.1-2), The self-polymerization precursor solution adopts a polymer conductive monomer-organic sulfonic acid compound solution, the polymer conductive monomer is selected from one or more of 3,4-ethylenedioxythiophene, 2,5-dithienylethylene, and pyrrole, the organic sulfonic acid compound is selected from one or more of 3-amino-4-hydroxybenzenesulfonic acid, o-aminoanisole-4-sulfonic acid, and 4-amino-2-hydroxybenzenesulfonic acid, and the usage ratio of the polymer conductive monomer to the organic sulfonic acid compound is (20-40 μL): (0.01-0.2 g).
2. The titanium implant with piezoelectric antibacterial properties according to claim 1, characterized in that: The solute of the electrospinning precursor solution is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, and hexamethylphosphoric triamide, and the dosage ratio of the semi-crystalline thermoplastic polymer to the solute is (0.1-0.5g):(1-5mL).
3. The titanium implant with piezoelectric antibacterial properties according to claim 2, characterized in that: When the semi-crystalline thermoplastic polymer, the piezoelectric material and the two-dimensional transition metal carbide are dissolved in a solute, ultrasonic treatment and heating and mixing are performed to obtain an electrospinning precursor solution. The frequency of the ultrasonic treatment is 5-20 kHz, the time is 10-30 min, and the temperature of the heating mixing is 60-100° C., the time is 2-6 h.
4. A method for preparing a titanium implant with piezoelectric antibacterial properties as claimed in any one of claims 1 to 3, characterized in that: The method comprises the following steps: S1, sequentially grinding and polishing, ultrasonic cleaning and vacuum drying the titanium material to obtain a pretreated titanium material, and performing dopamine polymerization on the pretreated titanium material; S2, immersing the titanium material in an electrospinning precursor solution for electrospinning; S3. Immerse the titanium material in a self-polymerizing precursor solution to perform self-polymerization, thereby obtaining a titanium implant with piezoelectric antibacterial properties.
5. The method for preparing a titanium implant with piezoelectric antibacterial properties according to claim 4, characterized in that: In step S1, the titanium material is polished using sandpaper with a mesh size of 320-800#. Use one or more of acetone, ethanol, and water to ultrasonically clean the titanium material. The frequency of a single ultrasonic cleaning is 5-20kHz and the time is 2-10min. The temperature of vacuum drying is 40-80°C, the vacuum degree is 0.03-0.1MPa, and the time is 10-30min.
6. The method for preparing a titanium implant with piezoelectric antibacterial properties according to claim 4, characterized in that: In step S1, the pretreated titanium material is immersed in a precursor solution for dopamine polymerization to polymerize dopamine, a buffer solution and a dopamine solution are dissolved in a solute and the pH is adjusted to obtain a precursor solution for dopamine polymerization. The buffer solution is selected from one or more of tris(hydroxymethyl)aminomethane hydrochloride solution, hydroxyethylpiperazineethanesulfonic acid solution, and borate buffer solution. The concentration of the buffer solution is 5-15 mmol / L. The dopamine solution adopts dopamine hydrochloride solution. The concentration of the dopamine solution is 0.5-1.5 g / L. The mass ratio of the buffer solution to the dopamine solution is (5-7):(3-5).
7. The method for preparing a titanium implant with piezoelectric antibacterial properties according to claim 6, characterized in that: The pH of the dopamine polymerization precursor solution is 8-9, The time for dopamine polymerization in step S1 is 24-48 hours.
8. The method for preparing a titanium implant with piezoelectric antibacterial properties according to claim 4, characterized in that: In step S2, the electrospinning flow rate is 0.5-1.5 mL / h, the applied voltage is 10-20 kV, the distance between the electrode and the titanium material is 10-20 cm, and the time is 1-3 h.
9. The method for preparing a titanium implant with piezoelectric antibacterial properties according to claim 4, characterized in that: The temperature of the self-polymerization in step S3 is 2-10° C. and the time is 12-36 hours.
10. Use of the titanium implant with piezoelectric antibacterial properties as claimed in any one of claims 1 to 3 in dental implant restoration.